Metal–organic frameworks as proton conductors: strategies for improved proton conductivity. Issue 31 (21st July 2021) - Biradha, Kumar; Goswami, Anindita; Moi, Rajib; Saha, Subhajit
Abstract : Various innovative strategies and methodologies for the development of MOFs and coordination polymers based materials for high performance solid state proton conductors and proton exchange membranes are outlined. Abstract : Recent studies on proton conductivity using pristine MOFs and their composite materials have established an outstanding area of research owing to their potential applications for the development of high performance solid state proton conductors (SSPCs) and proton exchange membranes (PEMs) in fuel cells (FCs). MOFs, as crystalline organic and inorganic hybrid materials, provide a large number of degrees of freedom in their framework composition, coordination environment, and chemically functionalized pores for the targeted design of improved proton carriers, functioning over a wide range of temperature and humidity conditions. Herein, our efforts have been emphasized on fundamental principles and different design strategies to achieve enhanced proton conductivity with appropriate examples. We also have discussed the modification mechanism of MOF-composite materials and mixed matrix membranes for commercial applications in FCs. Thus, this review aims to direct readers' attention towards the design strategies and structure–property relationship for proton transport in MOFs.